Anti‐fibrotic effects of different sources of MSC in bleomycin‐induced lung fibrosis in C57BL6 male mice. Issue 2 (26th August 2020) - Periera‐Simon, Simone; Xia, Xiaomei; Catanuto, Paola; Coronado, Ramon; Kurtzberg, Joanne; Bellio, Michael; Lee, Yee‐Shuan; Khan, Aisha; Smith, Robin; Elliot, Sharon J.; Glassberg, Marilyn K.
ABSTRACT: Background and objective: IPF is a fatal and debilitating lung disorder increasing in incidence worldwide. To date, two approved treatments only slow disease progression, have multiple side effects and do not provide a cure. MSC have promising therapeutic potential as a cell‐based therapy for many lung disorders based on the anti‐fibrotic properties of the MSC. Methods: Critical questions remain surrounding the optimal source, timing and efficacy of cell‐based therapies. The present study examines the most effective sources of MSC. Human MSC were derived from adipose, WJ, chorionic membrane (CSC) and chorionic villi (CVC). MSC were injected into the ageing mouse model of BLM‐induced lung fibrosis. Results: All sources decreased Aschroft and hydroxyproline levels when injected into BLM‐treated mice at day 10 with the exception of CSC cells that did not change hydroxyproline levels. There were also decreases in mRNA expression of αv ‐integrin and TNFα in all sources except CSC. Only ASC‐ and WJ‐derived cells reduced AKT and MMP‐2 activation, while Cav‐1 was increased by ASC treatment as previously reported. BLM‐induced miR dysregulation of miR‐29 and miR‐199 was restored only by ASC treatment. Conclusion: Our data suggest that sources of MSC may differ in the pathway(s) involved in repair. Abstract : MSC derived from adipose, chorion, villi and WJ were compared in their ability to rescue BLM‐induced lung fibrosis. Except for CSC, the fibrotic pathway activation was interrupted equally by all treatments; however, each source of MSC used a different mechanism to promote lung repair. See related Editorial